How do you multiply #(2x+3)(x^2+x-5)#?

1 Answer
Jun 25, 2015

Answer:

# = color(blue)(2x^3 + 5x^2 -7x -15#

Explanation:

#color(blue)((2x+3))(x^2 + x - 5)#

  • Here, we first multiply #color(blue)(2x) #contained in the first bracket with all three terms of second bracket:

# = color(blue)(2x).(x^2) + color(blue)(2x) .(x) + color(blue)(2x) . (-5)#

# = 2x^3 + 2x^2 -10x#........................#(1)#

  • Now, we multiply #color(blue)(3)# contained in the first bracket with all three terms of second bracket:

# = color(blue)(3).(x^2) + color(blue)(3) . x + color(blue)(3) . (-5)#

# = 3x^2 + 3x -15#.........................#(2)#

combining #(1)# and #(2)#

# = color(blue)(2x^3 + 5x^2 -7x -15#